Comparative study of carcinoembryonic antigen and epithelial membrane antigen expression in normal colon, adenomas and adenocarcinomas of the colon and rectum. Issue 9 (September 1989) - Davidson, B R; Sams, V R; Styles, J; Dean, C; Boulos, P B
Abstract : The heterogeneous nature of tumour antigen expression may require selection of monoclonal antibodies on an individual patient or tumour basis to allow adequate tumour localisation. Carcinoembryonic antigen (CEA) and epithelial membrane antigen (EMA) expression has not previously been compared in colorectal cancer patients. Sections of cancer (n = 52), adjacent normal colon (n = 45), synchronous adenomas (n = 11) and nodal metastases (n = 49) were examined by indirect immunoperoxidase staining in 51 consecutive patients with colorectal cancer using monoclonal antibodies to CEA and EMA. The percentage of cells with positive staining in the primary tumours was graded 1: less than 25%, 2: 25-49%, 3: 50-75%, 4 greater than 75%. All primary colorectal cancers expressed CEA and 43 of 52 expressed EMA (83%). Grading showed CEA greater than EMA in 39, equal in 11 and less in two. Well differentiated cancers were more frequently graded three or four for CEA staining (23 of 27) than moderately differentiated cancers (11 of 22) (p less than 0.01). Equivalent figures for EMA were four of 27 and three of 22 (not significant) (NS) although the majority (86%) were graded 1 and 2. Grade 1 CEA expression was found in six of 15 proximal and only two of 37 distal lesions (p less than 0.01, chi 2 test) while for EMA equivalent figures were three of 15 and six of 37 (NS). Nodal deposits all expressed CEA and 45 of 49 expressed EMA (92%); 29 of 45 normal colon sections showed CEA expression (64%) as did all adenomas. EMA was not expressed by normal colon or adenomas. These results suggest that EMA expression is more specific but less sensitive than CEA for colonic cancer and is independent of tumour differentiation and site. Thus selecting monoclonal antibodies to CEA or EMA based on tumour biopsies may allow improved tumour localisation for imaging or therapy in patents with colorectal cancer.